Generation left - Milburn, Keir. (Cambridge, UK : Polity Press, 2019)
Increasingly age appears to be the key dividing line in contemporary politics. Young people across the globe are embracing left-wing ideas and supporting figures such as Corbyn and Sanders. Where has this 'Generation Left' come from? How can it change the world? This compelling book by Keir Milburn traces the story of Generation Left. Emerging in the aftermath of the 2008 financial crash, it has now entered the electoral arena and found itself vying for dominance with ageing right-leaning voters and a 'Third Way' political elite unable to accept the new realities. By offering a new concept of political generations, Milburn unveils the ideas, attitudes and direction of Generation Left and explains how the age gap can be bridged by reinventing youth and adulthood. This book is essential reading for anyone, young or old, who is interested in addressing the multiple crises of our time.
Re : generations -- Generation left (behind) -- Generation explosion -- The electoral turn -- Reinventing adulthood.
Includes bibliographical references.
Keywords: Right and left (Political science); Young adults -- Political activity; Generations -- Political aspects; Age -- Political aspects